2003
DOI: 10.1016/s0304-405x(02)00252-0
|View full text |Cite
|
Sign up to set email alerts
|

Testing the pecking order theory of capital structure

Abstract: We test the pecking order theory of corporate leverage on a broad cross-section of publicly traded American firms for 1971 to 1998. Contrary to the pecking order theory, net equity issues track the financing deficit more closely than do net debt issues. While large firms exhibit some aspects of pecking order behavior, the evidence is not robust to the inclusion of conventional leverage factors, nor to the analysis of evidence from the 1990s. Financing deficit is less important in explaining net debt issues ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

92
1,081
18
86

Year Published

2010
2010
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 1,825 publications
(1,277 citation statements)
references
References 36 publications
92
1,081
18
86
Order By: Relevance
“…Other different studies such as: Ghosh et al (2000); Hadlock and James (2002); Frank and Goyal (2003), Berger and Bonaccorsi (2006), found a positive relationship between capital structure and firm's performance…”
Section: The Static Trade-off Theorymentioning
confidence: 85%
See 1 more Smart Citation
“…Other different studies such as: Ghosh et al (2000); Hadlock and James (2002); Frank and Goyal (2003), Berger and Bonaccorsi (2006), found a positive relationship between capital structure and firm's performance…”
Section: The Static Trade-off Theorymentioning
confidence: 85%
“…This result is aligned with the findings of Abu Rub (2012) in listed companies in Palestinian Security exchange. Other studies support this fact such as the study of Frank and Goyal (2003) and Hadlock and James (2002). Pratomo and Ismail (2006), that tested the impact of capital structure on banks performance in Malaysian banks where the findings showed that higher leverage is associated with higher profit efficiency in banks.…”
Section: The Static Trade-off Theorymentioning
confidence: 86%
“…We summarized that, there were relationship between debt and profitability (Ahmad et al, 2012;Ahmadinia et al, 2012;Shubita and Alsawalhah, 2012;Ching et al, 2011;Nadaraja et al, 2011;Frank and Goyal, 2003) and those variables also had relationship with business risk (Myers 2001;Kale et al, 1991;Marsh, 1982;Myers, 1977;Leland and Pyle, 1977;Lev, 1974), growth (Lim et al, 2012;San and Heng, 2011;Shah and Khan, 2007;Baker and Wurgler, 2002;Sunder and Myers, 1999;Homaifar et al, 1994;Myers, 1984;Lev, 1974), tangibility (Lim et al, 2012;Shamshur, 2010;Shah and Khan, 2007;Myers, 1984;Marsh, 1982) and size (Lim et al, 2012;Mohamad and Abdullah, 2012;Shamshur, 2010;Shah and Khan, 2007;Chen, 2004;Homaifar et al, 1994;Marsh, 1982). Then we developed the hypothesis for this study as follows:…”
Section: Hypothesis and Modelsmentioning
confidence: 97%
“…The other works, Myers (1984), added these relationship with growth and tangibility, while Mohamad and Abdullah (2012) and also Chen (2004) added with size. We noticed of some works about relationship debt, profitability and growth (San and Heng, 2011), relationship of debt and profitability (Nadaraja et al, 2011;Ahmadinia et al, 2012;Shubita and Alsawalhah, 2012;Ching et al, 2011;Frank and Goyal, 2003), relationship of debt, growth and size (Homaifar et al, 1994), relationship of debt, size and tangibility (Shamshur, 2010), relationship of debt, growth, size and tangibility (Shah and Khan, 2007;Lim et al, 2012), relationship of profitability, growth and business risk (Lev, 1974), relationship of debt and growth (Sunder and Myers, 1999;Baker and Wurgler, 2002) and the relationship of debt, size, bankruptcy risk and tangibility (Marsh, 1982).…”
Section: Ajasmentioning
confidence: 99%
See 1 more Smart Citation